1997
DOI: 10.1152/ajplung.1997.272.6.l1198
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production by rat alveolar macrophages can be modulated in vitro by surfactant protein A

Abstract: Alveolar macrophage and type II cells are known to generate nitric oxide, which is a highly reactive molecule that plays a role in host defense against pathogens, as well as tissue damage associated with inflammation in the lung. Both types of cells are known to generate the nitric oxide by inducible nitric oxide synthase (iNOS). Surfactant-associated protein A (SP-A) from various sources (human alveolar proteinosis, rat and recombinant rat) was found to upregulate nitric oxide production by alveolar macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
1
40
3
Order By: Relevance
“…Contrary to our current study, others have demonstrated a stimulatory influence of SP-A on AMs (39,40,66). The reasons why SP-A in some studies appears to stimulate AMs (39,40,66) and in others appears to dampen the AM response (36-38) is not clear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our current study, others have demonstrated a stimulatory influence of SP-A on AMs (39,40,66). The reasons why SP-A in some studies appears to stimulate AMs (39,40,66) and in others appears to dampen the AM response (36-38) is not clear.…”
Section: Discussioncontrasting
confidence: 99%
“…The reasons why SP-A in some studies appears to stimulate AMs (39,40,66) and in others appears to dampen the AM response (36-38) is not clear. There is some evidence that the method of isolation and purification of SP-A may alter SP-A function (39).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly observed alleles are 6A, 6A 2 , and 1A 5 for SP-A2 (10,24). Several studies have shown differences among human SP-A genetic variants expressed in vitro in their abilities to stimulate cytokine production (55,56) to bind carbohydrate (35) and lipids (16) and to enhance phagocytosis by alveolar macrophages (our unpublished observations).…”
mentioning
confidence: 63%
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%